A 50-bp Ins/Del polymorphism at the promoter region of the superoxide dismutase-1 and bipolar disorder type 1. (17th November 2017) - Kordestanian, Nazanin; Saadat, Mostafa
Abstract: Bipolar disorder type 1 (BPD) is a chronic psychiatric illness and is associated with oxidative stress. Superoxide dismutase-1 (SOD1; OMIM: 147450) metabolizes highly reactive and more dangerous superoxide radicals into less reactive molecules. A functional 50-bp insertion/deletion (Ins/Del) polymorphism in the promoter region of the gene has been reported. The primary aim of the current case–control study was to explore whether the SOD1 Ins/Del polymorphism associated with the risk of BPD. A secondary aim was to investigate the association between the study polymorphism and age of onset of BPD. The present case–control study was performed in Shiraz (southern Iran) on 228 BPD and 224 healthy blood donor controls. The genotypes of the SOD1 Ins/Del polymorphism were determined by polymerase chain reaction. There was no significant association between the genotypes of Ins/Del polymorphism and the risk of BPD. Using Cox proportional hazards regression model, after adjustment for family history of BPD, revealed a significant association between the SOD1 Ins/Del polymorphism and age of onset. The age of onset was significantly lower for the Del/Del genotype than the 'Ins/Ins + Ins/Del' genotypes (hazard ratio = 2.33, 95%CI: 1.08–5.02, p  = .030). Our present findings revealed that although the SOD1 Ins/Del polymorphism was not associated with the risk of BPD, it was significantly associated with age of onset of BPD.